Invasive cervical cancer in Ibadan: socio-sexual characteristic, clinical stages at presentation, histopathology distributions and HIV status (2019)
Background: Human Papillomavirus (HPV) infection persistence is the necessary but not sufficient cause of invasive cervical cancer (ICC). The effects of Human Immunodeficiency Virus (HIV) co-infection have been well documented. The purpose of this study was to describe our experience on the clinico-pathological characteristics of patients with cervical cancer and HIV status at a tertiary Hospital in Nigeria. Materials and Methods: This was a descriptive study among ICC patients presenting for clinical staging and biopsy for histological diagnosis at the Obstetrics and Gynaecology outpatient theatre of our hospital between January 2009 and February 2011. Results: Sixteen (6.8%) of the 248 patients with histologically confirmed ICC in this study were HIV positive. The mean age of all the participants was 55.4 (SD±10.2) years with the HIV positive patients’ younger than the HIV-negative and those that declined HIV testing. Coitarche was at lower age (18 [SD±4.4] vs 22[SD±3.4] years vs 24.5[SD±4.4], respectively). The modal lifetime sexual partners were four, one and two, respectively. Clinically, more HIV positive patients, presented at advanced stage of ≥ 2B. Also, the adenocarcinoma histological variant was slightly more among the HIV positive patients. Conclusion: HIV seemed relatively common among ICC patients and they presented at lower ages, at more advanced stages, earlier coitarche and more lifetime sexual partners. The proportion of adenocarcinoma histological types was slightly higher among the HIV positive patients compared with seronegative patients and those with unknown HIV status. Larger studies to substantiate these findings and ICC-HIV causal relationship are required.